Development of a methane-free, continuous biohydrogen production system from palm oil mill effluent (Pome) in cstr - Mansor, Mariatul Fadzillah; Md Jahim, Jamaliah; Mumtaz, Tabassum; Abd Rahman, Rakmi; Abd Mutalib, Sahilah (Taylor's University College, 2016)
This study aimed to develop the start-up experiment for producing biological hydrogen in 2 L continuous stirred tank reactor (CSTR) from palm oil mill effluent (POME) by the use of mixed culture sludge under non-sterile conditions. Besides using different source of starter culture, the effects of acid treated culture and various operating temperature from 35 °C to 55 °C were studied against the evolved gas in terms of volumetric H2production rate (VHPR) and soluble metabolite products (SMPs). The formation of methane was closely observed throughout the run. Within the studied temperature, VHPR was found as low as 0.71 L/L.d and ethanol was the main by-products (70-80% of total soluble metabolites). Attempts were made to produce biohydrogen without methane formation at higher thermophilic temperature (45-55 °C) than the previous range. The average of 1.7 L H2of 2 L working volume per day was produced at 55oC with VHPR of 1.16 L/L.d. The results of soluble metabolites also are in agreement with the volatile fatty acids (VFAs) which is higher than ethanol. Higher VFAs of 2269 mg/L was obtained with acetic acid being the main by-product. At this time methanogen has been deactivated and no methane was produced. From this study, it can be concluded that thermophilic environment may offer a better option in a way to eliminate methane from the biogas and at the same time improving hydrogen production rate as well.